The Global Health Security Index: Another Look - Goldschmidt, Peter G. (Frontiers in Epidemiology, 2022)
The Global Health Security Index (GHSI) was published in October 2019 (after more than 2 years in preparation); at about the same time that the COVID-19 pandemic (covid) started. The GHSI was intended to score countries' pandemic preparedness. Within months of the start of the pandemic, articles began to be published that claimed to assess the GHSI's validity. They correlated GHSI scores with countries' covid per capita death rates. They showed that the better prepared a country, the higher the death rate: a result that was counter to what would have been expected. This article takes another look at the GHSI by exploring the relationship in major European Union countries plus the United Kingdom. The analysis reported here confirms that early on the higher the GHSI score, the higher the covid per capita death rate (r=0.52, P<0.05). But, by the end of 2020, there was no correlation. By July 2021, the correlation was in the expected direction: the higher the GHSI score, the lower the covid per capita death rate (r=-0.55, P<0.05); ditto case fatality rate (r=-0.74, P<0.01). Further, the GHSI was better correlated with excess mortality, the best measure of pandemic impact (r=-0.69, P<0.01). However, per capita GDP was as good a predictor of excess mortality (r=-0.71, P<0.01) and the Health System Performance Index of case fatality rate (r=-0.71; P<0.01). By the end of 2021, the correlation between GHSI scores and covid per capita death rates had strengthened (r=-0.71; P<0.01). This exploratory analysis is not intended to produce generalizable conclusions about the effectiveness of countries' covid pandemic response management, which continues to evolve and hence can only be properly assessed after the pandemic has ended. Nevertheless, the following conclusions would seem to be warranted: 1) there seems to have been a rush to judge, or, at least, to publish, and 2) the validity of any forward looking pandemic preparedness score depends not only on being able to assess countries' capabilities but also being able to forecast what governments will (and will not) do in any given situation, a seemingly quixotic quest.